2020
DOI: 10.1007/s12105-019-01109-y
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Special Issue: Myoepithelial Neoplasms of Soft Tissue: An Updated Review with Emphasis on Diagnostic Considerations in the Head and Neck

Abstract: Primary myoepithelial neoplasms of soft tissue have been shown to be related to their salivary gland counterparts, with which they often share morphologic, immunophenotypic, and molecular genetic features, such as the presence of PLAG1 rearrangement in both soft tissue mixed tumor and salivary pleomorphic adenoma. However, important distinctions remain between soft tissue and salivary myoepithelial neoplasms, namely differing criteria for malignancy. This review provides an overview of the current understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…However, to confirm the diagnosis of an MT, appropriate immunohistochemical staining is needed. Studies have reported that MT mostly expresses epithelial antigens (cytokeratin and EMA) and S-100p [14] . This was not the case in our patient, who did not express S-100p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to confirm the diagnosis of an MT, appropriate immunohistochemical staining is needed. Studies have reported that MT mostly expresses epithelial antigens (cytokeratin and EMA) and S-100p [14] . This was not the case in our patient, who did not express S-100p.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case in our patient, who did not express S-100p. Vickie Jo reviewed the immunohistochemical features in MT and described that broad-spectrum cytokeratin is positive in 93–100% of cases, compared with a lower EMA positivity of 19–66% [14] . S-100p is positive in 72–100% of cases, and GFAP staining is lower, ranging from 27% to 54%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we further investigated the novel SRF::E2F1 fusion in myoepitheliomas, which, together with the mixed tumors/chondroid syringomas, represent a class of myoepithelial tumors of soft tissue with benign behavior [ 26 ]. In these samples, the expression of SRF::E2F1 transcript led to the production of a functionally active chimeric protein [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no validated grading system of myoepithelial carcinomas, although they can subjectively be graded into low, moderate, or high grade based on the degree of nuclear atypia and the presence of mitosis and necrosis. However, the histologic grading does not seem to predict behavior or prognosis (9). The lack of clearly defined or validated grading systems is reflected in the literature, where malignancy rarely is reported.…”
Section: Discussionmentioning
confidence: 99%